Popular Islamist Authoritative Parenting: A Contest of Identity in Islamic Education for Early Childhood - Mustakim, Bagus; Hasan, Noorhaidi; Lessy, Zulkipli (Yogyakarta: Jurusan Pendidikan Agama Islam Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2022)
Purpose – This article aims to explain the values of Islamism that are reproduced in animated videos of children, the religious style that is developed, and the identity of parenting that is constructed and contested. Design/methods/approach – The study was conducted qualitatively with a phenomenological approach, namely by constructing understanding, motivation, and parenting practices reproduced in animated videos. The primary data source is the animated film Nussa Data were collected through video documentation and analyzed by discourse analysis. Findings - It is concluded that: 1) the Islamism reproduced in the animation of Nussa leads to the development of Salafism values in early childhood care. 2) This development uses the Salafi religious style as a parenting style and practice which we call the popular Islamist authoritative parenting model. 3) This parenting model is encouraged to contest with other parenting models and serves as an identity that struggles to win religious authority in the field of early childhood care. Findings – It is concluded that: 1) the Islamism reproduced in the animation of Nussa leads to the development of Salafism values in early childhood care. 2) This development uses the Salafi religious style as a parenting style and practice which we call the popular Islamist authoritative parenting model. 3) This parenting model is encouraged to contest with other parenting models and serves as an identity that struggles to win religious authority in the field of early childhood care. Research implications/limitations – The data sources are limited to animated videos and sources on the Internet. There were no direct interviews with the informants but based on the narratives delivered directly through videos on various social media, especially Youtube. Originality/value – The findings of this study provide an overview of popular Islamist authoritative parenting that is promoted as a model of Islamic early childhood care.